FEATURES OF INTERPERSONAL RELATIONS, GENDER DIFFERENCES IN THE FORMATION OF INITIATIVE QUALITIES IN ADOLESCENTS - Mambetyarov Sharyar (Galaxy International Interdisciplinary Research Journal, 2024)
This article discusses the place of men and women in social life, the importance and structure of social groups, the analysis of social relations between elites and elites, the development of organizational abilities and the nature of people.